A proposal to account for the stimulus, the mechanism, and the mediators released in exercise-induced bronchoconstriction - Anderson, Sandra D.; Kippelen, Pascale (Frontiers in Allergy, 2023)
Exercise induced bronchoconstriction (EIB) describes the transient narrowing of the airways that follows vigorous exercise. It commonly occurs in children and adults who have asthma and in elite athletes. The primary stimulus is proposed to be loss of water, by evaporation, from the airway surface due to conditioning inspired air. The mechanism, whereby this evaporative loss of water provokes contraction of the bronchial smooth muscle, is thought to be an increase in osmolarity of the airway surface liquid. The increase in osmolarity causes mast cells to release histamines, prostaglandins, and leukotrienes. It is these mediators that contract smooth muscle causing the airways to narrow.